(untitled) (Research, Society and Development, 2021)
The purpose of this article is to analyze the meaning of conceptions and their forms of complexity in teaching/learning processes in the field of school Physical Education, specifically in quilombola education. Quilombola education takes place in communities through the sharing of knowledge and knowledge among everyone. The aim of the text is to present information about Quilombola School Physical Education, the challenges of its resistance and a pedagogical praxis that thematizes Afro-Brazilian culture. The adopted methodology consists of a qualitative analysis of bibliographic and interpretive nature, having as the main theoretical base Zabala, among others. In view of what was mentioned, we conclude that this article demonstrated that Quilombola education has been increasingly included with the aim of transmitting the knowledge and traditions of their culture, thus becoming extremely important, having Physical Education as a means. include this new knowledge in the classroom. In Zabala’s perspective, the assessment will be able to be divided and applied in four different contents, the same being the factual, conceptual, procedural and attitudinal, thus bringing each one with its own assessment concept, thus emphasizing the importance of education in the student’s life, thus, the school is a space for new knowledge and experiences.